Nature of association among spot blotch severity and some quantitative traits in bread wheat (Triticum aestivum L. em. Theil.) - and J.P. JAISWAL, PRASHANT GOEL*, SWATI, KANAK SRIVASTAVA (Indian Phytopathology, 2007)
A study was undertaken with six bread wheat genotypes crossed in 6 X 6 diallel design, excluding reciprocals to examine the nature of association between spot blotch severity and other quantitative traits. Simple correlation analysis revealed the significant positive correlation of spot blotch severity with plant height and spike length while significant negative association with days to heading, days to maturity, spike lets per spike, grains per spike, grain weight per spike, biological yield per plant and grain yield per plant. From the path coefficient analysis based on genotypic correlations, it was observed that grain weight per spike, days to heading, plant height and biological yield per plant had high negative direct effects on spot blotch severity. Thus, these characters may play major role in the formation of selection criteria for resistance to spot blotch in bread wheat.